CHALLENGES IN TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) - Fazildinova, Sevara Nematovna (Educational Research in Universal Sciences, 2024)
This thesis explores the effective teaching methodologies and strategies for English for Specific Purposes (ESP). ESP is a specialized branch of English language teaching that focuses on developing language proficiency in specific domains such as business, medicine, engineering, and tourism. The study investigates the theoretical foundations, pedagogical approaches, and practical implications of teaching ESP. By examining relevant literature and studies, this thesis aims to provide educators with valuable insights and recommendations for designing ESP courses and enhancing students’ language proficiency in their respective fields.